2017
DOI: 10.1039/c6ra26552a
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and photodegradation under visible light irradiation of an organic pollutant by a heterogeneous UiO-67–Ru–Ti MOF obtained by post-synthetic exchange

Abstract: By exchanging metals in a photoactive MOF, it has been possible to obtain a material for the photodegradation of methylene blue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 41 publications
2
32
0
1
Order By: Relevance
“…Due to a combination of positive features including flexibility in the design, wide selection of metals and organic linkers, possibility to incorporate co‐catalysts and large surface area, metal–organic frameworks (MOFs) are currently attracting considerable attention as photocatalysts to perform degradation of organic pollutants and for production of solar fuels …”
Section: Introductionmentioning
confidence: 99%
“…Due to a combination of positive features including flexibility in the design, wide selection of metals and organic linkers, possibility to incorporate co‐catalysts and large surface area, metal–organic frameworks (MOFs) are currently attracting considerable attention as photocatalysts to perform degradation of organic pollutants and for production of solar fuels …”
Section: Introductionmentioning
confidence: 99%
“…[11] Zirconium-MOFs, UiO-66 and 67 built with bdc (benzene-dicarboxylic acid) and bpdc (biphenyl-dicarboxylic acid) ligands respectively, have shown to possess very high thermal, chemical and water stability, [12] making them suitable as sorbents for environmental purposes. [13,14] Recently, we have shown that Zirconium-MOF UiO-66, with small cavity, can efficiently adsorb PFOX. [15] In this study, we evaluated the efficiency of UiO-67, with larger cavity, for the removal of PFOX in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…If a MOF is employed as light-sensitive semiconductor, the central metal-oxide cluster can be considered as a discrete QD, which is stabilized and interconnected by the organic linkers acting as photon antenna [26]. Compared with traditional semiconductor photo-catalysts, the superiority of MOFs originates from their ultrahigh surface area and narrow micropore distribution, which may lead to the formation of mono-disperse photoactive species supported on MOFs [27][28]. However, the photo-activity of MOF was not as effective as that of inorganic semiconductor NPs.…”
Section: Issn: 2320-5407mentioning
confidence: 99%